2014
DOI: 10.1016/j.pnpbp.2013.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Morphine-induced trafficking of a mu-opioid receptor interacting protein in rat locus coeruleus neurons

Abstract: Opiate addiction is a devastating health problem, with approximately 2 million people currently addicted to heroin or non-medical prescription opiates in the United States alone. In neurons, adaptations in cell signaling cascades develop following opioid actions at the mu opioid receptor (MOR). A novel putative target for intervention involves interacting proteins that may regulate trafficking of MOR. Morphine has been shown to induce a re-distribution of a MOR-interacting protein Wntless (WLS, a transport mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 116 publications
0
9
0
Order By: Relevance
“…Growing evidence suggests that the noradrenergic locus coeruleus (LC) is a major brain site involved in the onset of opioid withdrawal [41,42]. Neurons in the LC possess a high density of μ opioid receptors (MORs) [43]. When opioids bind to MORs in the LC, they suppress neuronal activity by inhibiting adenylyl cyclase-resulting in physical symptoms such as drowsiness, slow respiration, and low blood pressure [42].…”
Section: D3r and Opioid Withdrawalmentioning
confidence: 99%
“…Growing evidence suggests that the noradrenergic locus coeruleus (LC) is a major brain site involved in the onset of opioid withdrawal [41,42]. Neurons in the LC possess a high density of μ opioid receptors (MORs) [43]. When opioids bind to MORs in the LC, they suppress neuronal activity by inhibiting adenylyl cyclase-resulting in physical symptoms such as drowsiness, slow respiration, and low blood pressure [42].…”
Section: D3r and Opioid Withdrawalmentioning
confidence: 99%
“…Similarly, we have previously shown that Wls interacts with the MOR, DOR, and cannabinoid receptors type 1 and 2 albeit through different regions of the proteins (C-tail of Wls with IL2 of opioid receptors) [34, 36]. Opioid drug-induced internalization of MOR also drives the internalization of Wls in cells and in rat striatal dendrites [32, 54]. Morphine, an opioid agonist that delays MOR internalization, increases cell surface localization of Wls and decreases Wls recycling, resulting in an overall decrease in Wnt secretion [3234, 54].…”
Section: Discussionmentioning
confidence: 90%
“…Opioid drug-induced internalization of MOR also drives the internalization of Wls in cells and in rat striatal dendrites [32, 54]. Morphine, an opioid agonist that delays MOR internalization, increases cell surface localization of Wls and decreases Wls recycling, resulting in an overall decrease in Wnt secretion [3234, 54]. Future studies will assess whether GPM6a alters the constitutive recycling of Wls and whether GPM6a is important for co-internalization of Wls and MOR in cells treated with opioids that promote robust internalization.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, morphine has been showed to induce the secretion of Wnt signaling proteins (Jaremko et al, 2014). Besides, the opioids have many beneficial roles against the damage in central nervous system (Cui et al, 2011).…”
Section: Discussionmentioning
confidence: 99%